2016
DOI: 10.1371/journal.pone.0162641
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin, a Novel NF-κB Regulator, Is Required for Meningitic Escherichia coli K1-Induced Pathogen Invasion and PMN Transmigration across the Blood-Brain Barrier

Abstract: BackgroundNF-κB activation, pathogen invasion, polymorphonuclear leukocytes (PMN) transmigration (PMNT) across the blood-brain barrier (BBB) are the pathogenic triad hallmark features of bacterial meningitis, but the mechanisms underlying these events remain largely unknown. Vimentin, which is a novel NF-κB regulator, is the primary receptor for the major Escherichia coli K1 virulence factor IbeA that contributes to the pathogenesis of neonatal bacterial sepsis and meningitis (NSM). We have previously shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 64 publications
5
41
1
Order By: Relevance
“…LMP1 is an oncoprotein of EBV and expresses in most cells of EBV-associated NPC 3 , 24 , 25 . NF-κB, which has central functions in inflammation and cancer development 5 , 26 , is the main pathway activated by LMP1 27 . Besides the transforming ability, LMP1 has been noticed for its induction of invasion and metastasis recently 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…LMP1 is an oncoprotein of EBV and expresses in most cells of EBV-associated NPC 3 , 24 , 25 . NF-κB, which has central functions in inflammation and cancer development 5 , 26 , is the main pathway activated by LMP1 27 . Besides the transforming ability, LMP1 has been noticed for its induction of invasion and metastasis recently 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…When vimentin was knocked out in HBMEC cells, the infection rate of T. gondii was significantly increased (Figure 4 ). The result, indicating inhibition of host cell vimentin on T. gondii invasion, is opposite to those demonstrated for Escherichia coli K1 and Japanese encephalitis virus infection 31 , 46 , suggesting that vimentin regulates infection of T. gondii and other microbial pathogens by different mechanisms.…”
Section: Discussioncontrasting
confidence: 73%
“…Host cell vimentin has been demonstrated to function in facilitating the infection of some adhesive or invasive microbial pathogens, including P. multocida and African swine fever virus 29 , 30 . Moreover, vimentin is identified as a novel NF-κB regulator and is involved in modulating the NF-κB signaling pathway to influence invasion of pathogens, such as E. coli K1 31 , 32 . The disassembly of vimentin caused by treatment with high concentrations of the phosphatase inhibitors, okadaic acid and calyculin A, suggests that vimentin's assembly/disassembly is regulated by its phosphorylation and dephosphorylation 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that bacterial pathogens use vimentin as a receptor for host cell adherence to mediate pathogen entry into host cells or to cross host barriers ( 24 , 25 , 28 30 ). To examine the importance of vimentin for L. monocytogenes invasion in vitro , we performed gentamicin protection assays with MFT-6 (Vim +/+ ) and MFT-16 (Vim −/− ) mouse embryo fibroblasts ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, an increasing number of reports have demonstrated a diverse role for vimentin in bacterial infections, primarily in innate host cell defense mechanisms and pathogen adhesion and invasion ( 45 ). Vimentin has been shown to be an important invasion receptor for the IbeA protein of meningitic E. coli K1 and to facilitate invasion of the brain by E. coli K1 in vivo ( 24 , 28 , 46 ). We have shown for the first time that vimentin is exploited by L. monocytogenes for invasion and colonization of the brain in vivo .…”
Section: Discussionmentioning
confidence: 99%